2007
DOI: 10.1007/s10518-007-9049-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic soil-structure interaction effects on maximum inelastic displacement demands of SDOF systems

Abstract: This paper presents a statistical study of the kinematic soil-foundationstructure interaction effects on the maximum inelastic deformation demands of structures. Discussed here is the inelastic displacement ratio defined as the maximum inelastic displacement demands of structures subjected to foundation input motions divide by those of structures subjected to free-field ground motions. The displacement ratio is computed for a wide period range of elasto-plastic single-degree-of-freedom (SDOF) systems with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…With reference to the filtering action of the foundation, the important role of kinematic interaction has been established in the case of embedded foundations, where the foundation input motion can differ substantially from the free‐field motion at ground surface. The resulting effect is usually beneficial for squat structures while it may be detrimental for slender buildings with deeply embedded foundations or basements by increasing the ductility demand . The above has also been observed from recordings of instrumented buildings during real earthquakes, where, however, the recorded base slab motion stems from both inertial and kinematic interaction between the structure and the soil‐foundation system.…”
Section: Introductionmentioning
confidence: 82%
“…With reference to the filtering action of the foundation, the important role of kinematic interaction has been established in the case of embedded foundations, where the foundation input motion can differ substantially from the free‐field motion at ground surface. The resulting effect is usually beneficial for squat structures while it may be detrimental for slender buildings with deeply embedded foundations or basements by increasing the ductility demand . The above has also been observed from recordings of instrumented buildings during real earthquakes, where, however, the recorded base slab motion stems from both inertial and kinematic interaction between the structure and the soil‐foundation system.…”
Section: Introductionmentioning
confidence: 82%
“…However, soil-structure interaction causes a difference between the two because of the base slab averaging effect. The presence of stiff foundation As stated in the literature (Lin et al 2008& Hossein et al 2013, the main effect of kinematic interaction is to filter the high-frequency components of the free field motion, and the same is observed as detailed in the following figures, From the above plots, it is observed that the spectra of accelerations recorded at the base of the structure are de-amplified for all the cases when compared with the free field spectra for the same site condition. Hence, there is a reduction in seismic demand on the structures owing to the base slab averaging effect.…”
Section: Base Slab Averaging Effectsupporting
confidence: 65%
“…The ground motion accelerograms were collected from the PEER Strong Motion Database , the PEER Next Generation Attenuation database , and the COSMOS Virtual Data Center . Selected ground motions were recorded on free field stations or in the first floor or basement of low‐rise buildings with negligible soil‐structure interaction effects . It should be noted that the selected records were compiled from the datasets previously employed by Lu and Wei and Raghunandan and Liel .…”
Section: Model Parameters and Description Of Datasetmentioning
confidence: 99%